The pleasures of religion: and other poems ... - Pise, Charles Constantine (E. L. Carey & A. Hart, 1833)
Pleasures of religion.--The tourist.--Triumph of religion.--Thoughts on God.--Thoughts on man.--Conquest of Cozumel and Tabasco.--Miscellaneous poems.